Dimensionamento de elementos estruturais em concreto leve - Ferreira, Cláudia Nunes Gomes (Universidade Federal de São Carlos, 2015)
The lightweight concrete for structural purposes is a material that has great potential for application in various construction areas. Its main feature is the reduced density compared to conventional concrete. This characteristic is a great advantage, since one of the main shortcomings of conventional concrete is its heavy weight. Thus there is a reduction in foundation loads, reduction in moving cost due to smaller weight, low consumption cost of cement and, in some cases, improved thermal and acoustic performance. However, despite the great potential application of lightweight concrete, there is a lack of studies regarding the design criteria of elements made of this material type. The lightweight concretes have different strength properties when compared to conventional concrete, thus require special design criteria. As there is no specific Brazilian standard, the design is taken to be similar to the design principles of conventional concrete. In this context, the present study aims to evaluate design criteria for lightweight concrete elements in compression, shear and bending available in national and international standardization and specific technical literature. The study includes both the analysis of the design criteria for the Ultimate Limit State (ULS) and for checking the Limit State Service (LLS). Finally, cases are compared assessing beams, slabs and walls on four different types of lightweight concrete, taking into account factors such as material consumption, cost, weight and cement consumption.
Keywords: Concreto; Concreto leve; Dimensionamento; Materiais - especificações; Lightweight concrete; Design; Specification; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL